Improving vertical charge transport in organic Schottky diodes via interface engineering of large-area conducting polymer thin films fabricated on hydrophilic liquid surface of tunable surface energy - Jana S.; Kumari N.; Pandey S.S.; Prakash R. (My University, 2025)
Molecular orientation and stacking genre proved to be one of the decisive factors for the performance of conducting polymer (CP) based electronic devices. In this context, harnessing the key advantages of the ribbon shaped “floating-film transfer method” (FTM) along with an interfacial engineering approach has been utilized for molecular rearrangement in polymer thin-films formed on the surface of a high surface energy hydrophilic liquid mixture. In this novel subphase modified floating-film transfer method (SM-FTM), dodecyl benzene sulfonic acid (DBSA) has been used to control the molecular backbone stacking proximate to the solution-liquid interface and regioregular-poly(3-hexylthiophen-2,5-diyl) (rr-P3HT) was used as the model CP to probe the polymer-DBSA interaction. The molecular arrangements in microcrystalline domains, electronic band structures, and the evolution of surface texture at the solution-liquid interface have been investigated through multiple characterization tools. After that, the electrical performances of Schottky barrier diodes (SBDs) were studied in an ITO/P3HT/AlOx/Al sandwiched structure and a dramatic enhancement of rectification ratio up to 8.2 × 106 at ± 6 V was achieved. Further, an analytical model for SM-FTM, developed using lubrication theory and thin-film dynamics, has also been presented to elucidate the polymer spreading dynamics and the mechanism of molecular rearrangement at the interface. © 2023 Elsevier B.V.